Monitoring and analysis of air quality and meteorological parameters on the construction site by the IoT - Milivojević, Lazar B. (Vojnotehnički glasnik / Military Technical Courier, 2023)
Introduction/purpose: The construction industry is one of the main producers of dust, greenhouse gases and air pollutants. Effective operation and management of construction site operations can significantly reduce projects’ carbon footprints and other environmental impacts. Through the cooperation of a scientific and research institution and a construction company, the real-time monitoring of air quality at a construction site was implemented using IoT technologies. Methods: An IoT-based system framework that integrates a distributed sensor network to collect real-time data and demonstrates air quality at a construction site was implemented. Different types of sensors were used to collect data related to NO2, PM2.5, and PM10 particles, as well as meteorological parameters – wind speed and direction, humidity, pressure, and temperature. Results: The results of real-time measurements provide a picture of the state of air pollution at the construction site and the connection with construction activities that can be managed in order to reduce the concentration of polluting gases and suspended particles. Through on-site monitoring of a construction site in Belgrade City, this study found that the dust level due to construction activities is relatively high. Conclusion: It can be concluded that the construction activity had a significant impact on the air quality in the construction surrounding areas. Regarding the main factors affecting the building construction dust emission, the correlations show that building construction dust emission was not significantly correlated with meteorological factors.